Preconception Care: Concept Paper - Kufakunesu, Lilian; Shumba, Precious; Kapfunde, Abigail; Zvinavashe, Professor Matilda; Makoni, Doctor Petty (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Preconception care is lagging behind in most of the developing countries, yet it is a very criticalcomponent in maternal and child health. Preconception care is perceived as not very importantby most of the people and its difference with services provided at well women clinics is notclear. The objective of this concept analysis was to fully describe preconception care. Walkerand Avant model of concept analysis was used in helping to describe the concept of interest.Literature search was conducted in one month using Google Scholar, Pub-med and MEDLINE assearch engines. Twenty studies were reviewed and fifteen were found relevant in the descriptionof preconception care. The attributes, antecedents, consequences and empirical referents ofpreconception care were identified in the fifteen studies thereby defining preconception care as aset of interventions provided before conception for both males and females.